Power purchasing optimization of electricity retailers considering load uncertainties based on information gap decision theory. (November 2022) - Jiang, Xinyue; Li, Yating; Yu, Shuyang; Lin, Zhemin; Ji, Chao; Zhang, Zhi
Abstract: The optimization of power purchasing is the crucial part to enhance the core competitiveness of electricity retailers, which can help electricity retailers achieve economic efficiency improvement and risk reduction. Therefore, a power purchasing optimization model of electricity retailers based on IGDT is proposed in this paper. Firstly, considering the multiple uncertainties faced by electricity retailers when participating in the multi-time scale markets, the profits and risks of power purchasing strategies are quantified. Then, a power purchasing optimization model based on IGDT is constructed, which can assess the robustness of its purchasing strategies against load fluctuation under expected utility. Finally, the case studies using the data of a provincial power market in China illustrate that the proposed optimization model can effectively provide power purchasing strategies with robustness to balance the profit and risk of the electricity retailer, and as the risk attitude tends to be conservative, the proportion of power purchasing through bilateral contracts increases while the load fluctuation range that can be resisted decreases.